PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MELALUI PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN BIOLOGI SISWA KELAS X-10 SMA NEGERI 3 SURAKARTA TAHUN PELAJARAN 2011/2012 - Purnamaningrum, Arifah; Dwiastuti, Sri; Probosari, Riezky Maya; Noviawati, Noviawati (Pendidikan Biologi, 2012)
ABSTRACT ? The aim of this research was to improve creative thinking skill of students in class X-10 SMA Negeri 3 Surakarta year 2011/2012, which consist of 5 aspect, fluency, flexibility, originality, elaboration and evaluation. Classroom Action Research was used in this research, which has four phases, they are  planning, acting, observing, and reflecting. Data of the research were collected by using observation sheet, test, questionare, and interview. The data were analyzed by qualitative descriptive method. The validity of data was verified through triangulation technique of data collecting method. The results showed the percentage of every aspect of creative thinking skills based test on a first cycle have not gain thet targets, achievement of Fluency aspect is 69,70%, then 63.64% for Flexibility, 47.73% for Originality, 56.82% for Elaboration, and 49.24% for Evaluation. The results of the second cycle  increased, but there are aspects that have not reached the target. Result for each aspect was 79.55% for Fluency, 73.11% for Flexibility, Originality of 54.55%, 60.23% for Elaboration, and Evaluation of 57.58%. All aspects have not fulfill of the target yet, so the action continued to third cycle. The results achieved in the third cycle, Fluency aspects of 85.86%, 78.03% for flexibility, 63.64% for Originality, 60.23% for Elaboration, and Evaluation of 62.12%. All aspects of creative thinking skills already outreach the target, so the action was stopped. The conclusion of this research described that the Problem Based learningn (PBL) improve creative thinking skill in biology subject learning of students at class X-10 SMA Negeri 3 Surakarta year 2011/2012. Key Word : Problem Based Learning Model, Creative Thinking Skill